PEMBERDAYAAN DESA BRILIAN - Derriansya Putra Jaya; Isma Nirmala; Edwar Juliartha (Jurnal Pengabdian Pasca Unisti (JURDIANPASTI), 2023)
Community service activities are carried out for 3 months, namely online training for 2 months with a total of 8 training sessions for all participating villages and offline assistance for the 3 best training participants for 1 month and a minimum of 4 times. The empowerment objects in the Brilian Village program consist of: (1) Village officials (Village Head), (2) BUMDes administrators, (3) Village Consultative Body, (4) Village Business Actors (including village business clusters). Based on the results of the dedication: (1) Villages can optimize all village potential (both natural, human and superior commodities) on an ongoing basis (sustainability), (2) Villages can apply/compile financial reports and utilize banking financial services, especially BRI, (3) Villages can take advantage of digital technology for village progress both in activities and village financial management, (4) BUMDes can manage businesses on an ongoing basis as a driving force for the village economy